Reading Hebrews through Akan ethnicity and social identity - Kissi, Seth (HTS teologiese studies, 2017)
The Akan people of Ghana have concepts of ethnicity and social identity which are similar to those found in the Mediterranean world, which find expression in the issues addressed in the letter to the Hebrews. This similarity makes the reading of Hebrews in light of Akan ethnicity and social identity possible, giving one the expected meaning from the perspective of those concepts as within the original context of the audience. This article therefore discusses some theories on ethnicity and social identity as well as the Akan people of Ghana and their concepts of ethnicity and social identity. It further explains the social context of the letter of Hebrews against which Hebrews is then read in light of Akan ethnicity and social identity. The focus of this reading is on how the ethnic identity of the readers presented in Hebrews enhances the social identity of the readers and provides the means by which the author’s appeal to his readers for their faithfulness to God becomes meaningful and urgent.